Cenozoic evolution of the Southern Andes: morphotectonic and geochronologic approaches and insights from analog modeling - Guillaume, Benjamin (CCSD, 2008)
The geomorphological and thermochronological studies carried out in the central Patagonia show the influence of the Chile spreading-ridge subduction on the surface dynamics. During the last 14 Myr, the migration of the triple junction between the Nazca, Antarctic and South America plates towards the north goes hand in hand with a long-wavelength uplift. It affects the Patagonian Andes, where Apatite (U-Th)/He ages are younger south of the triple junction (~7-5 Ma) than north of it, but also the basin located east of the mountain chain where terraces, emplaced since middle Miocene, are tilted in the N-S direction with values of 0.1-0.2%. These values correspond to the ones expected from semi-analytical analysis of dynamic topography. Analogue modeling of the subduction process shows the interaction between processes at depth and surface dynamics: we observe a link between variations of the slab dip and deformation of the overriding plate and we study the effects of the opening of a slab window. L'étude géomorphologique et thermochronologique menée en Patagonie centrale montre l'influence de la subduction de la dorsale du Chili sur la dynamique de surface. Depuis 14 Ma, la migration vers le nord du point triple entre plaques Nazca, Antarctique et Amérique du Sud s'accompagne d'un soulèvement de grande longueur d'onde. Celui-ci affecte les Andes de Patagonie, où les âges (U-Th)/He sur apatite sont plus jeunes au sud du point triple (~7-5 Ma) qu'au nord, mais aussi le bassin à l'est de la chaîne, où les terrasses mises en place depuis le Miocène moyen ont subi des basculements N-S de ~0,1-0,2%. Ces valeurs correspondent à celles prévues par des calculs analytiques de topographie dynamique. Des modèles analogiques du processus de subduction montrent les interactions entre processus profonds et dynamique de surface : nous observons un lien entre changement de pendage du slab et déformation de la plaque supérieure, et étudions les phénomènes liés à l'ouverture d'une fenêtre de slab.